Stress Sonography of the Ulnar Collateral Ligament of the Elbow in Professional Baseball Pitchers: A 10-Year Study - Ciccotti, Michael G. (2014)
BACKGROUND: An injury to the ulnar collateral ligament (UCL) of the elbow is potentially career threatening for elite baseball pitchers. Stress ultrasound (US) of the elbow allows for evaluation of both the UCL and the ulnohumeral joint space at rest and with stress. HYPOTHESIS: Stress US can identify morphological and functional UCL changes and may predict the risk of a UCL injury in elite pitchers. STUDY DESIGN: Cross-sectional study; Level of evidence, 3. METHODS: A total of 368 asymptomatic professional baseball pitchers underwent preseason stress US of their dominant and non-dominant elbows over a 10-year period (2002-2012). Stress US examinations were performed in 30° of flexion at rest and with 150 N of valgus stress by a single musculoskeletal radiologist. Ligament thickness, ulnohumeral joint space width, and ligament abnormalities (hypoechoic foci and calcifications) were documented. RESULTS: There were 736 stress US studies. The mean UCL thickness in the dominant elbow (6.15 mm) was significantly greater than that in the nondominant elbow (4.82 mm) (P < .0001). The mean stressed ulnohumeral joint space width in the dominant elbow (4.56 mm) was significantly greater than that in the nondominant elbow (3.72 mm) (P < .02). In the dominant arm, hypoechoic foci and calcifications were both significantly more prevalent (28.0% vs 3.5% and 24.9% vs 1.6%, respectively; P < .001). In the 12 players who incurred a UCL injury, there were nonsignificant (P > .05) increases in baseline ligament thickness, ulnohumeral joint space gapping with stress, and incidence of hypoechoic foci and calcifications. More than 1 stress US examination was performed in 131 players, with a mean increase of 0.78 mm in joint space gapping with subsequent evaluations. CONCLUSION: Stress US indicates that the UCL in the dominant elbow of elite pitchers is thicker, is more likely to have hypoechoic foci and/or calcifications, and has increased laxity with valgus stress over time.